“It has Changed, Quite Clearly.” Exploring Perceptions of German Police Trainers on Police Recruits - Koerner, Swen; Staller, Mario S. (Frontiers in Education, 2022)
The individual views and attitudes of trainers responsible for equipping police officers for operational demands have rarely been subject to international research. Geared toward the German situation, the following case study focuses on the particular question of how police trainers at a German state police training site perceive police recruits as the target group of their coaching. The data set consisted of n = 8 interviews with police trainers who were originally conducted with the aim to investigate their expert opinions on pedagogical, training-related issues. Within the process of inductive coding, the perceived recruit condition emerged as a high-order theme, displaying a predominantly deficit-oriented view among police trainers. The findings are discussed through the lens of the concept of critically reflective practice, in which the reflection of the views and guiding assumptions of the police trainers is seen as a key ingredient for a further professionalization of the police trainer education and its respective research.